Wittgenstein's Philosophical investigations : a reader's guide - Ahmed, Arif (Continuum reader's guides., 2010)
Ludwig Wittgenstein's Philosophical Investigations is a hugely important piece of philosophical writing, one frequently encountered by students of philosophy. Yet, there is no escaping the extent of the challenge posed by Wittgenstein's work, in which complex ideas are often enigmatically expressed. In Wittgenstein's 'Philosophical Investigations': A Reader's Guide, Arif Ahmed offers a clear and thorough account of this key philosophical work. Geared towards the specific requirements of students who need to reach a sound understanding of the text as a whole, the book offers guidance on:. - Ph.